Seasonal Variations in the Fish Species Composition and Community Structures on the Eastern Coast of South Korea - Jeonghoon Han; Young-Ung Choi (Journal of Marine Science and Engineering, 2022)
The seasonal variations in the species composition of set net fisheries were investigated on the Eastern coast of Korea, from 2007 to 2008. In total, 51 species were found that were classified into 15 orders and 33 families. The water temperature of the study area was 0.1–1.8 °C in 2007 and 0.6–2.1 °C in 2008, which was higher than the average water temperature in the previous decade. The monthly variation in the number of species peaked twice, in May (spring) and November (autumn) when the water temperature increased and decreased, respectively, and the monthly variation in the number of individuals showed a remarkably high trend in winter and autumn and was mainly caused by large migratory species. Based on the cluster analysis of the 18 most dominant species with more than 0.4% of the total number of individuals, we divided the species composition and community structures into three groups: fishes with a temporary appearance (Group A), fishes with a long-term appearance (Group B), and dominant pelagic fishes appearing with a long-term appearance (Group C). We could conclude that the seasonal variation in the structure of the fish community was mainly caused by the pelagic migration of species under high water temperature conditions during the study period.